Factors affecting prepubertal and pubertal bone age progression - Satoh, Mari; Hasegawa, Yukihiro (Frontiers in Endocrinology, 2022)
Bone age (BA) is a clinical marker of bone maturation which indicates the developmental stage of endochondral ossification at the epiphysis and the growth plate. Hormones that promote the endochondral ossification process include growth hormone, insulin-like growth factor-1, thyroid hormone, estrogens, and androgens. In particular, estrogens are essential for growth plate fusion and closure in both sexes. Bone maturation in female children is more advanced than in male children, at all ages. The promotion of bone maturation seen in females before the onset of puberty is thought to be an effect of estrogen because estrogen levels are higher in females than in males before puberty. Sex hormones are important for bone maturation during puberty. Since females have their pubertal onset about two years earlier than males, bone maturation in females is more advanced than in males during puberty. In the present study, we aimed to review the factors affecting prepubertal and pubertal BA progression, BA progression in children with hypogonadism, and bone maturation and deformities in children with Turner syndrome.